Self-management education for rehabilitation inpatients suffering from inflammatory bowel disease: a cluster-randomized controlled trial. Issue 6 (20th September 2016) - Reusch, A.; Weiland, R.; Gerlich, C.; Dreger, K.; Derra, C.; Mainos, D.; Tuschhoff, T.; Berding, A.; Witte, C.; Kaltz, B.; Faller, H.
Abstract : Although inflammatory bowel disease (IBD) affects patients' psychological well-being, previous educational programs have failed to demonstrate effects on psychosocial outcomes and quality of life. Therefore, we developed a group-based psychoeducational program that combined provision of both medical information and psychological self-management skills, delivered in an interactive manner, and evaluated it in a large, cluster-randomized trial. We assigned 540 rehabilitation inpatients suffering from IBD (mean age 43 years, 66% female) to either the new intervention or a control group comprising the same overall intensity and the same medical information, but only general psychosocial information. The primary outcome was patient-reported IBD-related concerns. Secondary outcomes included disease knowledge, coping, self-management skills, fear of progression, anxiety, depression and quality of life. Assessments took place at baseline, end of rehabilitation and after 3 and 12 months. The psychoeducational self-management program did not prove superior to the control group regarding primary and secondary outcomes. However, positive changes over time occurred in both groups regarding most outcomes. The superior effectiveness of the newly developed psychoeducational program could not be demonstrated. Since the intervention and control groups may have been too similar, this trial may have been too conservative to produce between-group effects.